Da teologia política à ontologia política: a profanação e a política que vem no projeto Homo sacer de G. Agamben - Mota, Thomaz Fernandes Rocha (2019)
This dissertation follows Mathew Abbot’s reading of Agamben’s works, highlighting the relevance of Giorgio Agamben’s political ontology, i.e. his engagement on the question of the political stakes of the question of being. Posing that question we start from Agamben’s notion of the sacred as men’s alienation from their potentialities through the sacrifice apparatus to present Agamben’s alternative to political theology. We argue Agamben’s political philosophy consciously offers counterpoints to Carl Schmitt’s Political Theology. Addressing the relation between Schmitt’s political theology and his concept of the political, presupposed on his concepts of the constitution and his theory on “movements”, we argue that Agamben’s political thought engages with the Schmittian notions of theology and the political to overcome the logic underlying his thought. We posit that Agamben’s critique implies a different understanding of the religious phenomena that stresses out its cultic aspects, opening for a discussion of the religious aspects in capitalism, a reading influenced by Walter Benjamin’s Capitalism as Religion. With a new understanding of the sacralization apparatus, a different task for the overcoming of political theology is implied: the profanation, the restitution of what was previously removed from free use to the common use of men.